Polysulfide dissolution control: the common ion effect - Shin, Eon Sung; Kim, Keon; Oh, Si Hyoung; Cho, Won Il (ROYAL SOC CHEMISTRY, 2013)
A Li-sulfur cell with a high discharge capacity of over 1300 mAh g(-1) at a C/10 rate, and a controlled overcharge amount less than 1%, was manufactured by synthesizing a carbon-sulfur nano-composite via a wet milling process, and suppressing polysulfide dissolution using an electrolyte with a highly concentrated lithium salt.
Keywords: ELECTROCHEMICAL PROPERTIES; SULFUR; CATHODE; PERFORMANCE; CARBON; ELECTROLYTE; COMPOSITES; BATTERIES; MECHANISM